Immunohistochemical Analysis of Cancer Stem Cell Marker Expression in Papillary Thyroid Cancer - Kim, Hye Min; Koo, Ja Seung (Frontiers in Endocrinology, 2019)
Cancer stem cell (CSC) markers have prognostic significance in various cancers, but their clinical significance in papillary thyroid carcinoma (PTC) has not been demonstrated. In this study, CSC markers expressed in PTC and their relationships with prognosis were evaluated. We constructed tissue microarrays for 386 PTC cases, divided it into 42 low risk cases and 344 intermediate risk cases according to the American Thyroid Association 2009 Risk Stratification System. Immunohistochemical staining of CSC markers (CD15, CD24, CD44, CD166, and ALDH1A1) was performed, and the proportion of stained cells and immunostaining intensity were evaluated to determine positive marker expression. The relationships between CSC marker expression and other clinicopathological parameters or survival were analyzed. CD15 expression was higher in PTC with intermediate risk than in PTC with low risk (29.4% vs. 11.9%, p = 0.017). According to a multivariate analysis, CD15, CD44, CD166, and ALDH1A1 positivity were independently associated with a shorter progression-free survival (PFS) (odds ratio [OR]: 1.929, 2.960, 7.485, and 3.736; p = 0.016, p = 0.026, p < 0.001, and p = 0.006, respectively). Higher N and cancer stage were the only other clinical factors associated with a shorter PFS (OR: 2.953 and 1.898, p = 0.011 and p = 0.034). Overexpression of CSC markers in PTC was associated with shorter PFS during follow-up. Immunohistochemical staining of CSC markers may provide useful information for predicting patient outcomes.